HUBUNGAN POLA ASUH ORANG TUA DENGAN PERILAKU SEKSUAL REMAJA PUTRI DI SMA NEGERI 5 LHOKSEUMAWE - Hendrika Wijaya Kartini Putri; Nurmila Nurmila; Rosyita Rosyita (STIKes Murni Teguh, 2021)
The rapid growth experienced by adolescents leads them to have a great sense of curiosity in various things without disolved the first information that they can. This makes teenagers fall into the negative. One of the negative things that become a teen problem is teenage sexual behavior. The purpose of this study is to determine the relationship between the characteristics and parenting patterns of parents with the sexual behavior of girls in high school 5 Kota Lhokseumawe in 2019. This research type is analytic observational research by using cross sectional approach method. The population in this research were female students in SMA 5 Kota Lhokseumawe in 2019 class XI which amounted to 96 people. Data analysis in this research used unvariat and bivariate. The findings of this research obtained that parenting patterns have a meaningful relationship with the sexual behavior of young girl adolescent in SMA Negeri 5 Kota Lhokseumawe. for parenting pattern obtained p <0.05, which means there is a relationship between parenting parenting with the sexual behavior of young girl. It is expected that students will participate in training and extracurricular activities in schools such as joining the Youth Reproductive Health program to improve adolescent about risky sexual behavior. Parents are expected to provide child care and sex education as early as possible to the children by of open communication, listening to each other and keeping an eye on their child's association so as to avoid irresponsible sexual behavior of teenagers. Abstrak Pesatnya pertumbuhan yang dialami oleh remaja menyebabkan mereka memiliki rasa ingin tahu yang besar dalam berbagai hal tanpa larut terlebih dahulu informasi yang mereka dapat. Hal ini membuat remaja terjerumus ke dalam hal yang negatif. Salah satu hal negatif yang menjadi masalah remaja adalah perilaku seksual remaja. Tujuan penelitian ini adalah untuk mengetahui hubungan antara karakteristik dan pola asuh orang tua dengan perilaku seksual anak perempuan di SMA Negeri 5 Kota Lhokseumawe Tahun 2019. Jenis penelitian ini adalah penelitian observasional analitik dengan menggunakan metode pendekatan cross sectional. Populasi dalam penelitian ini adalah siswa perempuan di SMA Negeri 5 Kota Lhokseumawe kelas XI 2019 yang berjumlah 96 orang. Analisis data dalam penelitian ini menggunakan unvariat dan bivariat. Hasil penelitian ini diperoleh bahwa pola asuh memiliki hubungan yang bermakna dengan perilaku seksual remaja putri di SMA Negeri 5 Kota Lhokseumawe. untuk pola asuh diperoleh p < 0,05 yang berarti ada hubungan pola asuh dengan perilaku seksual remaja putri. Diharapkan siswa mengikuti pelatihan dan kegiatan ekstrakurikuler di sekolah seperti mengikuti program Kesehatan Reproduksi Remaja untuk meningkatkan pengetahuan remaja tentang perilaku seksual berisiko. Orang tua diharapkan memberikan pengasuhan anak dan pendidikan seks sedini mungkin kepada anak melalui komunikasi yang terbuka, saling mendengarkan dan mengawasi pergaulan anaknya sehingga terhindar dari perilaku seksual remaja yang tidak bertanggung jawab.